Psicología del desarrollo de la edad adulta Teorías y contextos - Izquierdo Martínez, Ángel (Revista Complutense de Educación, 2006)
The article provides an overview of central aspects in the developmental psychology of elderly adults. Despite the central focus being on age, it will be based on a life-span perspective that delineates developmental guidelines for general change and stability, as well as for those typical in certain phases of the lifecycle. The approach presented here is centred around questions about the aging person, their resources, goals coping with specific and typical requirements of age, developmental contexts as well as the respective target processes employed. For that purpose, first the developmental psychology of aging will be defined. This will be followed by a description of the most important theoretical concepts and their position in the context of the approach presented here. Finally, a characteristic chronology of competencies in old age will be delineated.
Keywords: old age; competencies; resources; developmental psychology; life-span